2022
DOI: 10.2147/jir.s331303
|View full text |Cite
|
Sign up to set email alerts
|

SAHA Alleviates Diarrhea-Predominant Irritable Bowel Syndrome Through Regulation of the p-STAT3/SERT/5-HT Signaling Pathway

Abstract: Objective Irritable bowel syndrome (IBS) is characterized by abdominal pain, bloating, and stool irregularity. However, its pathophysiological mechanisms, which trigger intestinal motility disorders and diarrhea leading to diarrhea-predominant IBS (D-IBS), remain largely unknown. Methods In the present study, we established a D-IBS rat model by mother–infant separation combined with restraint stress. Then we exposed the modelled rats to suberoylanilide hydroxamic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Stressful life events can lead to various mental and gastrointestinal disorders, including IBS-D. Rat models such as restraint stress and maternal separation can cause visceral hypersensitivity, anxiety-like behavior, and abnormal intestinal motility and diarrhea, which are among the pathological and physiological mechanisms of IBS-D. 28,29 AWR is a reliable indicator for assessing visceral sensitivity in IBS-D. 30 Our results revealed that there was no statistically significant difference observed among the three groups at a pressure of 0.2 ml ( p > Food & Function Paper 0.05 for all pairwise comparisons). As the applied pressure increased, the AWR scores in the IBS-D group were significantly higher than that in the Ctrl group, while the AWR scores in the Li05 group exhibited a significant decrease compared the IBS-D group ( p < 0.05) (Fig.…”
Section: Li05 Alleviated Diarrhea and Visceral Hypersensitivity In Ib...mentioning
confidence: 99%
“…Stressful life events can lead to various mental and gastrointestinal disorders, including IBS-D. Rat models such as restraint stress and maternal separation can cause visceral hypersensitivity, anxiety-like behavior, and abnormal intestinal motility and diarrhea, which are among the pathological and physiological mechanisms of IBS-D. 28,29 AWR is a reliable indicator for assessing visceral sensitivity in IBS-D. 30 Our results revealed that there was no statistically significant difference observed among the three groups at a pressure of 0.2 ml ( p > Food & Function Paper 0.05 for all pairwise comparisons). As the applied pressure increased, the AWR scores in the IBS-D group were significantly higher than that in the Ctrl group, while the AWR scores in the Li05 group exhibited a significant decrease compared the IBS-D group ( p < 0.05) (Fig.…”
Section: Li05 Alleviated Diarrhea and Visceral Hypersensitivity In Ib...mentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is a gastrointestinal disorder that is characterized by altered defecation habits, abdominal discomfort, and abdominal pain. It is said that IBS affects the lives of 10–15% of the global population [ 1 ]. Since IBS is the most prevalent functional gastrointestinal disorder (FGID) in chronic visceral pain [ 2 , 3 , 4 , 5 ], we selected it as the investigatory target in this study representing chronic visceral pain.…”
Section: Introductionmentioning
confidence: 99%